Great Muslims Scientists in the Most Glorious Human Centuries and in so called Dark Ages of the West! - Haque, Anwar Ul (International Journal of Pathology, 2018)
With coming of the final Prophet Muhammad peacebe upon him (PBUH) (570-622) big bang occurred inall fields of Sciences and Social Sciences. This wasthe time when entire West was submerged in totaldarkness and hence this period is known as “Darkages” in history. But this was the time period in theMuslim land which can be labeled as Most GlitteringCenturies in the history of mankind. As the ProphetPBUH left this world the seeds he sowedgerminated into small plants which soon grew intotall trees and dense forest of human development.